Cloud Privacy and Security- A Review Paper - Rajan Jha; Nikita Kumari; Chidera Carol Omeribe (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Distributed computing has revolutionized the way people use cloud resources to host and deliver various services through the internet. The benefits of cloud resources are many, and with the rapid development of cloud technology, it has become more accessible to users. However, one major issue that needs attention is cloud security. Many users are still unaware of the risks associated with cloud storage, and there is a lack of mass awareness on this issue. As cloud technology continues to gain traction in the corporate world, clients need to be aware of the standards of cloud utilization. However, many clients may lack knowledge about IT security, which can be a major risk. It is crucial to measure the level of their understanding and develop a training framework to promote security awareness. This is where new measurements and calculations for assessing security familiarity come in. By incorporating emerging cloud security requirements, we can better equip corporate clients and workers with the necessary knowledge to use cloud resources safely and securely.